Do shocks affect men's and women's assets differently? A review of literature and new evidence from Bangladesh and Uganda - Quisumbing, Agnes R.; Kumar, Neha; Behrman, Julia A. (International Food Policy Research Institute, 2011)
This background paper attempts to expand our understanding of the gender-differentiated impact of shocks on assets through a literature review on shocks and gendered asset dynamics and an analysis of new panel data (2007 and 2009) from Uganda and Bangladesh looking at the impact of negative shocks and positive events on men's and women's assets. We take advantage of detailed assets and shocks modules to disaggregate the type of shock between covariate and idiosyncratic shocks and types of assets according to ownership (joint, husband's, and wife's assets). We also consider the impact of life-cycle events such as dowry payments and receipts, and inheritance. Estimation of an asset accumulation regression as a function of covariate and idiosyncratic shocks, with controls for baseline characteristics and asset stocks, finds that although many shocks are similar in both countries, commonly experienced shocks do not necessarily have the same effects across countries and on men's, women's, and jointly owned assets within countries. Land and assets in general were relatively well insured against food price increases in Bangladesh, but jointly held assets and wives' assets in Uganda were negatively affected. Weather shocks negatively impact husbands' assets and wives' assets in Bangladesh and Uganda, respectively. Reflecting differences in country and context, dowry and wedding expenses took their toll on wives' land in Bangladesh, and illness shocks also had a large detrimental impact on wives' assets in Bangladesh, while death negatively affected wives' assets in Uganda. Within households, however, it appears that in Bangladesh, husbands' land and assets were more negatively affected by covariate shocks relative to wives' assets, whereas in Uganda, husbands' assets were relatively protected against covariate shocks relative to wives' assets.